Karakterisasi Media Tanam dari Kombinasi Cocopeat dan Pupuk Kandang Ayam - Nadia Nuraniya Kamaluddin; Reginawanti Hindersah; Diana Nafitri Cahayaningrum; Putri Sri Judiani Purba; Diky Indra Wibawa; Mieke Rochimi Setiawati (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
Indonesia is one of the largest coconut (Coconus nucifera L.) producing country in the world. Cocopeat can be mixed with chicken manure because of its relatively higher nutrient content compared to other manures. Cocopeat and chicken manure mixture can be an alternative to soilless planting media to support sustainable agriculture. In this study, the chemical and biological characters of cocopeat and chicken manure mixture were analyzed. Five different of combinations of cocopeat and chicken manure mixture: A (1: 1), B (2: 1), C (1: 2), D (2: 3), E (3: 2) were used as treatment. A Completely Randomize Design (CRD) with two replications were used. Data were analyzed with Independent T-test methods. The lowest C/N (33,39) was from D treatment (2:3), highest P2O5 content (0,08%) by C treatment (2:1), highest K2O content (0,03%) from A treatment (1:1) as control, the highest Ca-dd content (31,3%) was E treatment (3:2), and the highest Mg-dd content (1,45%) was obtained from control. All treatments reached the minimum moisture content limit for planting media. The total number of highest bacteria (161 x 107 cfu/g) is showed by D treatment (2:3), and the highest fungi level (58 x104 cfu/g) shown by C treatment (2:1).